Evaluation of excessive noise exposure among construction workers in South Quay Square (SQS), Sunway City, Kuala Lumpur. - Cheong, Win Sern (2024)

(untitled)
The construction industry in Malaysia have been making a substantial contribution to the economic development in the current era. However, researchers have found that the involvement of on-site mechanization and the excessive noise produced from the utilization of machineries and power tools in construction sites are a main contributor to the development of hearing loss symptoms among construction workers in the construction industry. The noise level generated from the machinery and power tools on site was reported to have exceeded the daily noise exposure level of 85 dB(A) which specified in the Occupational Safety and Health (Noise Exposure) Regulations 2019. Therefore, the continually exposure to noise level exceeding 85 dB(A) can resulted in hearing diseases such as hearing impairment, hearing disorders, Noise Induced Hearing Loss (NIHL), presbycusis, and tinnitus. A total of 4 similar exposed groups (SEGs) was selected from construction site in Sunway City, Kuala Lumpur: SEG 1 hacking activities, SEG 2 formwork dismantling, SEG 3 falsework dismantling, and SEG 4 aluminium formwork installation. A point monitoring was carried out in all SEGs to determine the noise exposure levels and compared them with the noise levels written in Noise Risk Assessment (NRA) report. Subsequently, a validated and adopted questionnaire "Self-Evaluation of Hearing Status’ was distributed to the construction workers in all SEGs. The questionnaire focused on socio-demographic, lifestyle, and occupational factors to determine the prevalence of hearing loss among 50 respondents. The results were then transferred to Statistical Package of the Social Science (SPSS) version 21 to conduct a chi-square test on determining the significant risk factors that contributing to the development of hearing loss symptoms among construction workers using chi-square test. Furthermore, the comparison of noise levels obtained from point monitoring showed less variations to the noise levels written in the NRA report. The noise exposure levels obtained from point monitoring based on selected SEGs were between 86.7 and 97.8 dB(A), while the noise exposure levels stated in the NRA report were between 89.0 and 96.7 dB(A), which in both cases showed that the daily noise exposure level of 85 dB(A) was exceeded. Meanwhile, the results showed that 20% of them have severe hearing loss symptoms, 48% of them have hearing loss symptoms from acute to mild, and 32% of them have no hearing loss symptoms. Additionally, socio-demographic, lifestyle, and occupational factors were found significantly contributed to the development of hearing loss symptoms such as age (p=0.012), level of education (p=0.05) and smoking habits (p=0.014), Hearing Protective Devices (HPDs) (p=0.044), duration of employment (p=0.002), working days (p=0.004), and working hours (p=0.026). To sum up, the predicting factors that were found to be associated with hearing loss symptoms among construction workers were age, level of education, smoking habits, wearing HPDs while working, duration of employment, working days, and working hours. Recognizing the hearing loss symptoms at an early age is crucial, especially for those who have prolonged exposure to excessive noise in construction sites. Therefore, this study helps in identifying the risk factors which could lead to hearing loss symptoms among construction workers and providing suitable control measures as recommendations to be considered in managing construction noise, hence preventing the likelihood of occupational noise-related hearing loss cases within a rapidly industrializing country like Malaysia.